STUDI TENTANG DALALAH MAKNA : ABSOLUTISME DAN RELATIFISME AYAT-AYAT HUKUM DALAM AL-QUR’AN - Zuhri, Saifudin (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2015)
Al-Qur?an is a hammalat li al-wujuh, so that from meaning searching aspect famous with an expression, someone doesn?t called mufasir except if he can to give various interpretation toward every verses of al-Qur?an. That is way from the expert of usul and fuqaha inclined give interpret to the al-Qur?an as Allah?s word in meaning lafzi word, because their purpose is for instinbat al ahkam. With hammalat li al wujuh sure will give the different of law comprehension, even may be happen contradiction in interpretation a verses of ahkam. In term of usul fiqh absolute and relative oftenconnected with their technical term about qat?i and zanni in realize verses of dalalah. Verses that showing absolute is qat?i and which showing relative is zanni. Relativism is concepts which declare that a life value is relative, different according to the conditions development, culture, etc. Conversely absolutism looks at that life a value doesn?t change, not relative, but absolute although conditions, culture, and the other experience change. Especially in law side, appear the questions whether law verses in al-Qur?an there has absolute and don?t know law development existence causes period development.It is time for the experts doesn?t base on analyses harfiyah-tekstual on law verses which has qat?i. should always understood that ahkam verses thinking building fundamental harmony, humanity universals or social justice. Individual interpretation offer towards provision both for qat'i also peace that can to guarantee humanity harmony in the eyes of Islam valid. Approach barer, easy to dialogue and contextual towards verses ahkam with integration in society life make easy to popularizing fiqh. on the basis of this so law consistence that appointed based on verses ahkam may not quit of mawasid al-hukm li jalbi al-masalih wa dar?i al-mafasid.